Application of Co3O4 as anode catalyst in CO2 electrolyzer cells - Attila Kormányos; Tatiana Priamushko; Gergely F. Samu; Angelika Samu; Balázs Endrődi; Serhiy Cherevko; Csaba Janáky (NPG Asia Materials)
Abstract Replacing Ir with anode catalyst materials that are more abundant is a long-sought objective within the CO2 electrolysis community. The chemical environment (near-neutral pH, carbonate buffer electrolyte) that inherently develops during long-term operation, however, limits the pool of applicable candidates. In this contribution, Ir was replaced with a porous Co3O4 nanosheet catalyst layer as the anode of a zero-gap CO2 electrolyzer cell. The catalyst was directly deposited on the Ti porous transport layer via hydrothermal synthesis, which allowed the precise control of the catalyst loading. Under optimal conditions (7 mg cm-2 Co3O4 loading), 300 mA cm-2 current density was reached at 3.4 V applied cell voltage. The electrolyzer cell with the Co3O4 anode was operated continuously for 50 hours at 250 mA cm-2 current density with stable cell voltage and CO2 reduction selectivity.